Entangled Trajectory Molecular Dynamics Theory for the Collinear $H+H_2$ Reaction (Journal of Atomic and Molecular Sciences, 2014)
The recently formulated entangled trajectory molecular dynamics (ETMD) theoryis applied to the collinear hydrogen exchange reaction. The reaction probability is calculatedfor one- and two-dimensional of collinear $H+H_2$ model. It is found that although the results ofETMD are not in good agreement with quantum mechanics simulations, the numerical trend isconsistent with each other.
Keywords: quantum phase space; Wigner function; entangled trajectory molecular dynamics.